New Media Insights from Indonesia in the 2024 Election: Wawasan Media Baru dari Indonesia dalam Pemilu 2024 - Juli, Asmaul Khusna Tri Wulan; Iskandar, Rayhan Rizq; Abadi, Totok Wahyu (House of Wisdom: Journal on Library and Information Sciences, 2024)
This research delves into how new media, especially social platforms, shapes positive perceptions, with a focus on politicians vying for the presidency in Indonesia's 2024 election. Using bibliometric analysis, data from 2014-2023 in the Crossref database were examined, revealing 1000 papers with 244 citations. VOSviewer software visualized the impact of new media on candidates' public image, highlighting areas for further research. The study underscores social media's crucial role in political branding and its influence on voter perception, crucial for candidates' success. Highlight: New media's impact on political image. Bibliometric analysis of Crossref data. Role of social media in political campaigns. Keyword: New media, Social media, Political branding, 2024 presidential election, Public perception.